Design and Creation of Ready-to-Wear Deluxe Muslim Fashion Inspired by Minakjinggo and Damarwulan Costumes - Awanda Alisa Fitriyah; Deny Arifiana (Journal of Creative Industries and Vocational Innovation, 2026)
This practice-led study explores the transformation of the contrasting visual characteristics of Minakjinggo and Damarwulan costumes from the Banyuwangi Janger performance into a ready-to-wear deluxe Muslim fashion collection. The study aims to describe the exploration, design development, realization, and presentation of the collection. The creative process followed four stages: exploration, design, realization, and presentation. During exploration, the visual characteristics of the two characters were identified through silhouette, color, garment structure, and decorative elements. Thirty alternative designs were developed for adult women, adult men, and girls. Following a design review by two fashion experts, three designs were selected for realization. The collection integrates Minakjinggo’s bold ornamentation with Damarwulan’s structured and balanced appearance through layered forms, contrasting colors, pompons, dangling sequins, and laser-cut Gajah Oling motifs. The works were presented at the 37th UNESA Annual Fashion Show Madjadhikara 2025, where the girls’ design received the Best Kids Fashion Design award in the Muslim fashion category. The study demonstrates how costumes from local performing arts can be transformed into contemporary Muslim fashion without reproducing the traditional costumes literally.